Influence of Fine Aggregate Ratios on the Performance of Lightweight Polyurethane Concrete from EMC Waste - Muhamad Afnan Hasri; Abdullah, Mohd Sufyan; Harun, Hasnida; Kosnin, Hilmi (Progress in Engineering Application and Technology, 2026)
The rapid generation of electronic waste (e-waste) has become a significant environmental concern, necessitating innovative recycling strategies in the construction industry. The objective of this research is to investigate the possibility of recycling silicon dioxide SiO₂ from Epoxy Molding Compound (EMC) waste to serve as a sustainable filler for Lightweight Polyurethane Concrete (LWPC). In this study, SiO₂ was derived from EMC waste through a thermal decomposition (pyrolysis) process at an isothermal temperature of 500°C for 5 minutes and subsequently sieved to a particle size of 425 µm to ensure optimal micro-filling capability. The experimental program was designed to partially substitute 5% of Ordinary Portland Cement (OPC) with the reclaimed EMC silica and an additional 5% of Silica Fume across three different sand-to-cement ratios, specifically 2.5%, 3.0%, and 3.5%. The physical, mechanical, and thermal properties of the composites were rigorously examined following a 28-day air-curing period. The findings revealed that all EMC-modified mixes yielded densities of less than 1920 kg/m³, successfully identifying them as structural lightweight concrete according to ASTM C567 standards. Among the tested proportions, mix 2 (Ratio 3.0) was found to be the optimal composition, achieving a compressive strength of 1.34 MPa, which outperformed the control sample’s 1.30 MPa due to the effective micro-filling action and pozzolanic reactivity of the EMC particles. Furthermore, the introduction of EMC particles refined the pore structure, reducing water absorption to 22.72% and enhancing thermal insulation performance. Mix 2 achieved a thermal conductivity value of 0.423 W/mK, representing an 8.4% improvement in insulation compared to the control sample. These results demonstrate that recycled EMC waste is a viable alternative supplementary cementitious material for non structural applications, such as partition walls, contributing to a circular economy and a sustainable building environment.